Uprawnienia Konferencji Biskupów w zakresie prawa o sakramentach św. - Janczewski, Zbigniew (Prawo Kanoniczne, 1997)
This article shows one of lawgivers - the Bishops Conference who can make the law of sacraments in the particular Church. Tells about rights of the Conference on the question of constitute the sacramental law. The first part of the article is about competences which the Bishops Conference has from Vaticanum II, the second part about the competences from post Vaticanum legislation. The third part shows competences which Code of Canon Law 1993 gives to Conference.